Potential harms from legalization of recreational cannabis use in Canada - Windle, Sarah B. (Can J Public Health, 2019)
With the recent legalization of recreational cannabis use in Canada, questions remain concerning optimal regulation to minimize harms and ensure public health and safety. Patterns of use are subject to change following legalization, and it is important to consider the potential adverse effects that this may have on public health. Important areas of consideration are methods of consumption (e.g., vaping, edibles) and product proliferation; acute and long-term health and behavioural effects (including impaired driving); and use in vulnerable groups, such as children and youth, pregnant women, individuals with mental illness, individuals with low socio-economic status, and Indigenous populations. To support harm reduction measures and evidence-based policy, there is a need to anticipate the potential ramifications that legalization of recreational cannabis use may have on public health in Canada.